Trans-Boundary Harm: A Primer on International Environmental Jurisprudence - Sharma, Rangam; Mathur, Anisha (Kathmandu School of Law Review, 2013)
The paper discusses international jurisprudence in the regime of transboundary harm. Principles of good neighbourliness, due diligence and precaution are major guidelines forwarded by international jurisprudence dealing with trans-boundary problems. The paper examines the current status quo of customary and conventional international law that acts as a tool to combat trans-boundary harm. The paper ponders into the issues of territorial sovereignty, doctrine of necessity and conventional obligations to prevent transboundary harm making extensive use of the judicial and arbitral decisions to throw light on the existing regulations and obligation. The paper concludes that effects of customs, conventions, treaties and other international instruments have led to establishment of effective mechanism to determine the liability and the quantum of liability.